Microeconomics : principles and policy - Baumol, William J.; Blinder, Alan S. (Fort Worth : Dryden Press, 1997)
Economics
Keywords: Microeconomics; Economic problem; Supply; Demand; Consumers; Production; Cost; Price; Profit; Market system; Industry; Labor; Poverty; Taxation